2023
DOI: 10.28991/cej-2023-09-05-012
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Seismic Hazard Analysis to Determine Liquefaction Potential Due to Earthquake

K. A. Hanindya,
Lalu Makrup,
. Widodo
et al.

Abstract: The great rocking of building structures and the occurrence of liquefaction in water-saturated soil on river banks are generally caused by earthquake shaking. The waves generated by the earthquake are the main cause of the shaking. In order to show the effect of ground motion earthquake shaking on the response of structures and liquefaction processes, it is necessary to analyze the structure and liquefaction as well as the time history of artificial earthquake ground motions. An artificial time history for liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…To show the effect of earthquake on the response of structures, it is necessary to use the time history of earthquake. Earthquake vibration data is required for the design of tall buildings or large-scale structures such as dams or bridges (41). In the present paper, the vertical and horizontal components of the Taft Earthquake were used in dynamic analyses of the Koyna Dam, as shown in Figures 2 and 3.…”
Section: Finite-element Modeling Of the Koyna Dammentioning
confidence: 99%
“…To show the effect of earthquake on the response of structures, it is necessary to use the time history of earthquake. Earthquake vibration data is required for the design of tall buildings or large-scale structures such as dams or bridges (41). In the present paper, the vertical and horizontal components of the Taft Earthquake were used in dynamic analyses of the Koyna Dam, as shown in Figures 2 and 3.…”
Section: Finite-element Modeling Of the Koyna Dammentioning
confidence: 99%
“…Eq (6) indicates that the cumulative distribution function (CDF) of P f is a log normal distribution. Therefore…”
Section: Theory Of Fragility Analysis and Life Cycle Estimationmentioning
confidence: 99%
“…Traditionally, seismic design has relied on deterministic approaches [6], which consider earthquakes as singular events with predetermined characteristics. However, this approach fails to capture the inherent uncertainties associated with seismic hazards and their impact on structural response [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various techniques, including in-situ and experimental methods to assess the potential of liquefaction for several soils. For instance, based on spectral matching to a target spectrum, Hanindya et al (7) developed an artificial time history of earthquake to study the liquefaction of a stratified ground and concluded that liquefaction potential reduces with increasing stiffness and depth of soil. Cone Penetration Test (CPT) results can also be employed to determine the liquefaction potential.…”
Section: Introductionmentioning
confidence: 99%